Protective effects of yacon (Smallanthus sonchifolius) intake on experimental colon carcinogenesis - de Moura, Nelci A. [UNESP]; Caetano, Brunno F. R. [UNESP]; Sivieri, Katia [UNESP]; Urbano, Luis H. [UNESP]; Cabello, Cláudio [UNESP]; Rodrigues, Maria A. M. [UNESP]; Barbisan, Luis F. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
Yacon (Smallanthus sonchifolius), a tuberous root native to the Andean region of South America, contains high concentration of fructans with potential for colon cancer prevention. This study investigated the potential beneficial of yacon intake on colon carcinogenesis induced by 1,2-dimethylhydrazine (DMH) in male Wistar rats. After 4 weeks of DMH-initiation, groups were fed basal diet (Cl and G6) or basal diet containing dried extract of yacon root at 0.5% (G2), 1.0% (G3 and G5) or a synbiotic formulation (G4) (1.0% yacon plus Lactobacillus casei at 2.5 x 10(10) CFU per g diet) for 13 weeks. At week 20, a significant reduction in number and multiplicity of aberrant crypt foci (ACF) and in number of invasive adenocarcinomas was observed in the groups orally treated with 1.0% yacon (G3) or the synbiotic formulation (G4) (0.05 < p < 0.001). Tumor multiplicity (noninvasive plus invasive) was significantly lower in the group fed synbiotic formulation (p < 0.02). A significant reduction in cell proliferation in colonic crypts and tumors and short chain fatty acids (SCFA) caecal contents was observed in the groups orally treated with 1.0% yacon (G3) or the synbiotic formulation (G4). Therefore, the findings this study indicate that yacon and yacon plus L casei intake may reduce the development of chemically-induced colon cancer. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Yacon root; Colon carcinogenesis; Cancer chemoprevention; Rat